Guidelines for Developing Participatory Management in Schools under the Nakhon Ratchasima Municipality - Teebklang, Pongsakron; Tiamvong, Veerapong; Chanawong, Kasama (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this research were to 1) study on current situation, desirable condition, and needs for the Management with Participation in school under the Nakhon Ratchasima Municipality and 2) study Guidelines for developing the Management with Participation in school under the Nakhon Ratchasima Municipality. This research was done by Mixed Methods Research. The sample group consisted of 148 school administrators and teachers Krejcie and Morgan Table. They were selected by Stratified random sampling and Simple random sampling. The research instruments contained the five-rating scaled questionnaires the semi-structured interview form and the Assess suitability and feasibility from. The data analysis statistics were the percentage, mean, standard deviation, modified priority needs Index (PNI modified), and content analysis. The results of the research were as follows: 1. current conditions, desirable condition, and priority needs the Management with Participation in school under the Nakhon Ratchasima Municipality. The overall of current conditions were at high level (x̄ = 3.60). The overall of current conditions were at highest level (x̄ =4.87). Priority needs the Management with Participation in school under the Nakhon Ratchasima Municipality are arranged in order from highest to lowest as follows: 1) Participation in decision-making 2) Participation in planning 3) Participation in benefits 4) Participation in inspection and evaluation and 5) Participation in operations. 2. Guidelines for developing the Management with Participation in school under the Nakhon Ratchasima Municipality, consists of 5 aspects: 1) Participation in decision-making had 3 guidelines 2) Participation in planning had 3 guidelines 3) Participation in benefits had 3 guidelines 4) Participation in inspection and evaluation had 3 guidelines and 5) Participation in operations had 3 guidelines. The total was 15 guidelines. The appropriateness was at a highest level, an average of (x̄ =4.97) and the feasibility was at a highest level, an average of (x̄ =4.82).